The difference of Bishop score change and labor event between oral and vaginal misoprostol in pregnancy beyond 41 weeks - Maskasoni Maskasoni; Julian Dewantiningrum (Majalah Obstetri & Ginekologi, 2023)
HIGHLIGHTS Oral misoprostol is more effective than vaginal misoprostol in cervical ripening as a part of induction of labor. Oral misoprostol is as safe as vaginal misoprostol.   ABSTRACT Objective: To compare Bishop score changes and labor event between oral and vaginal misoprostol in pregnancy beyond 41 weeks. Materials and Methods: A total of 52 pregnant women with more than 41 weeks of gestation, had a Bishop score less than 5, and were undergoing induction labor were randomly divided into two groups: oral and vaginal misoprostol. In the oral misoprostol group, participants were given 25 mg of misoprostol in a solution with a concentration of 1 ug/ml every 2 hours. In the vaginal misoprostol group, a 25 mg misoprostol tablet was inserted into the posterior fornix every 6 hours. The two groups were compared in terms of Bishop score during the first 6 hours, changes in Bishop score, labor at term events, neonatal outcomes, complications, and side effects after the administration of misoprostol. Results: The oral group showed significantly higher changes in Bishop score compared to the vaginal group (5.5 vs 3.6; p=0.0001). The median interval times for induction of labor at term, induction at stage II, and induction at birth were found to be shorter in the oral misoprostol group compared to the vaginal group (7.3 hours vs 10.6 hours, 14.0 hours vs 16.8 hours, and 14.6 hours vs 17.6 hours; p=0.002, 0.003, 0.002). Labor at term occurred much more frequently in the oral group (53.8% vs 15.4%). Additionally, the oral misoprostol group had a 3.5 times higher likelihood of experiencing labor at term within the first 6 hours after the initial administration compared to the vaginal group (OR 3.5, 95% CI 1.33-9.23). Conclusion: Oral administration of misoprostol for cervical ripening has been demonstrated to be more effective than vaginal administration, greater bishop score changes while maintaining an equivalent level of safety.